Rustoyburu, Cecilia (2019). La medicalización de la infancia: Florencio Escardó y la Nueva Pediatría en Buenos Aires. Ciudad Autónoma de Buenos Aires: Editorial Biblos. Pp. 304. - Bruschetti, Lucas (Ejes de Economía y Sociedad, 2020)